Radiological presentation of chondromyxoid fibroma in the sellar region: A CARE-compliant article and literature review. Issue 49 (December 2017) - Shen, Shuai; Chen, Miao; Jug, Rachel; Yu, Cheng-Qian; Zhang, Wan-Lin; Yang, Lian-He; Wang, Liang; Yu, Juan-Han; Lin, Xu-Yong; Xu, Hong-Tao; Ma, Shuang
Abstract: Rationale: Chondromyxoid fibroma (CMF) is a rare benign bone neoplasm which often occurs in the lower extremities. Little is known about the radiological and histological presentation of CMF in the sellar region. Patient concerns: A 16-year-old Asian male presented to the hospital 12 months ago with bilateral diplopia involving right visual fields, intermittent headaches, and dizziness. Interventions: After the patient underwent enough examinations, the lesion was surgically removed by curettage. Diagnosis: Postoperatively, the lesion was pathologically confirmed to be CMF. Outcomes: There was no recurrence at the 12-month follow-up. Lessons: To the best of our knowledge, this is the second reported case of CMF in the sellar region which was clinically suspected to be a pituitary macroadenoma, craniopharyngioma, or schwannoma due to its location and radiographic features. We reviewed the morbidity, symptoms, radiographic features, pathological findings, and differential diagnosis of CMF. Because of its rarity, attention should be paid to avoid misdiagnosis of this lesion.